Combined exome sequencing and deep phenotyping in highly selected fetuses with skeletal dysplasia during the first and second trimesters improves diagnostic yield. (12th June 2021) - Zhang, Xinyue; Ren, Yuan; Song, Rui; Wang, Longxia; Xu, Hong; Xie, Xiaoxiao; Zhou, Honghui; Sun, Pei; Zhang, Manli; Zhao, Qingdong; You, Yanqin; Gao, Zhiying; et al.
Abstract: Objective: To investigate the genetic etiology of skeletal dysplasia in highly selected fetuses during the first and second trimesters using deep phenotyping and exome sequencing (ES). Method: Fetuses with short femurs were identified using the established prenatal diagnostic approach. A multidisciplinary team reviewed fetal phenotypic information (prenatal ultrasound findings, fetal postmortem, and radiographs) in a cohort of highly selected fetuses with skeletal dysplasia during the first and second trimesters. The affected families underwent multiplatform genetic tests. Results: Of the 27 affected fetuses, 21 (77.8%) had pathogenic or potential pathogenic variations in the following genes: COL1A1, FGFR3, COL2A1, COL1A2, FLNB, DYNC2LI1, and TRIP11 . Two fetuses had compound heterozygous mutations in DYNC2LI1 and TRIP11, respectively, and the other 19 carried de novo autosomal dominant variants. Novel variants were identified in COL1A1, COL2A1, COL1A2, DYNC2LI1, and TRIP11 in 11 fetuses. We also included the first description of the phenotype of odontochondrodysplasia in a prenatal setting. Conclusions: ES or panel sequencing offers a high diagnostic yield for fetal skeletal dysplasia during the first and second trimesters. Comprehensive and complete phenotypic information is indispensable for genetic analysis and the expansion of genotype–phenotype correlations in fetal skeletal abnormalities. Key Points: What's already known about this topic? Short fetal femur length is associated with non‐genetic and genetic causes. Exome sequencing (ES) is a powerful tool to identify pathogenic variants, and has been widely adopted in prenatal diagnosis. ES has a variable diagnostic yield for various fetal structural abnormalities. What does this study add? Deep phenotyping facilitates bioinformatics analysis of ES in fetal skeletal dysplasias. Panel sequencing and ES have a high diagnostic yield for highly selected fetuses with skeletal dysplasias in the first and second trimesters.